2006
DOI: 10.2463/mrms.5.197
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Locus Ceruleus on Neuromelanin Magnetic Resonance Imaging at 3 Tesla

Abstract: Purpose: To investigate age-related changes in the locus ceruleus (LC) in healthy subjects using neuromelanin magnetic resonance (MR) imaging at 3 Tesla.Methods: We examined 64 healthy volunteers (aged 23 to 80 years) using neuromelaninsensitive T 1 -weighted images and measured the contrast of areas of high signal intensity corresponding to the LC.Results: A pair of punctate areas of high signal intensity that represented neuromelanin within the noradrenergic neurons of the LC was easily recognized in all sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
177
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(198 citation statements)
references
References 18 publications
16
177
3
2
Order By: Relevance
“…By using multidirectional images, we could visualize the three-dimensional distributions of the SNc, and observed distributions were closely correlated with those described in neuroanatomic textbooks (Figure 3). Neuromelanin-sensitive MRI also visualizes bilateral areas of rod-shaped high signal intensity within the pontine tegmentum, immediately anterolateral to the fourth ventricle floor at the level of the upper pons (Figures 2 and 3) [2,3]. The location was identical to that of the LC in the gross specimen, suggesting that the high-signal spots reflect the neuromelanin in the noradrenergic neurons of the LC.…”
Section: How Does Mri Enable the Visualization Of Neuromelanin?mentioning
confidence: 79%
See 2 more Smart Citations
“…By using multidirectional images, we could visualize the three-dimensional distributions of the SNc, and observed distributions were closely correlated with those described in neuroanatomic textbooks (Figure 3). Neuromelanin-sensitive MRI also visualizes bilateral areas of rod-shaped high signal intensity within the pontine tegmentum, immediately anterolateral to the fourth ventricle floor at the level of the upper pons (Figures 2 and 3) [2,3]. The location was identical to that of the LC in the gross specimen, suggesting that the high-signal spots reflect the neuromelanin in the noradrenergic neurons of the LC.…”
Section: How Does Mri Enable the Visualization Of Neuromelanin?mentioning
confidence: 79%
“…The neuronal number and intraneuronal neuromelanin content of the SNc and LC change substantially with age [27,28]. Our preliminary study showed a significant age-dependent variance in the signal intensity of the LC [3]; this variance should be considered while evaluating signal alteration. The iron concentration in the SNc neurons, which strongly influences the T1-shortening effects of neuromelanin [13], is increased in normal subjects with aging and in PD patients [28,29].…”
Section: What Are the Limitations And Future Prospects Of Neuromelanimentioning
confidence: 98%
See 1 more Smart Citation
“…On neuromelanin-sensitive MR axial images, it is identified as a spotty high signal intensity area in the upper pontine tegmentum [17,20] (Fig. 3).…”
Section: Locus Ceruleusmentioning
confidence: 99%
“…In a new set of experiments, the same authors have recently demonstrated a positive correlation between continuous pupil diameter and BOLD activity in a dorsal pontine cluster overlapping with the LC by simultaneously recording pupilometry and fMRI both at rest and during performance of a two-stimulus oddball task (Murphy, O'Connell, O'Sullivan, Robertson, & Balsters, 2014). LC was localized via both neuromelaninsensitive structural imaging (Shibata et al, 2006) and a previously published LC atlas (Keren, Lozar, Harris, Morgan, & Eckert, 2009). This relationship was present with and without spatial smoothing of the fMRI data, and survived retrospective image correction for physiological noise (Glover, Li & Ress, 2000).…”
Section: Pupil Diameter As An Indirect Index Of Lc Activitymentioning
confidence: 99%